MENENTUKAN FORECAST PRODUKSI SUMUR DAN MENGHITUNG ORIGINAL OIL IN PLACE DENGAN METODE STRAIGHT LINE MATERIAL BALANCE RESERVOIR MINYAK PADA LAPANGAN Y - Bonifasius Aristomo Haryo Adi; Onnie Ridaliani; Rida Husla (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2019)
The purpose of calculating the Original Oil In Place (OOIP) is to know the potential of reservoir to be produced. Calculation of OOIP in field Y based on determining the type of drive mechanism at the beginningfollowed by calculation the value of Underground Withdrawal and parameters of fluid expansion. All parameters then used to draw the graphic using Havlena and Odeh Method. The value of OOIP is 354,766 MMSTB.Along with the time and production activity, the OOIP will be reduced. Therefore it is important to forecast the production itself. Constant Decline is determined using Trial Error and X2 Chisquare Test Method with value of constant decline b = 0 and decline rate 0,01855. This means that the type of decline curve is exponential curve. This type of decline curve is used to forecast the production until q economic limit. As a result, the value of Estimated Ultimated Recovery is 296,0386 MMSTB, Recovery Factor 83,4461%, and Remaining Reserve 51,9415 MMSTB. Keyword: Original Oil In Place, Decline Curve Analysis, material balance straight line, Recovery Factor, Remaining Reserve